Epigenetic Mechanisms Involved in the Cardiovascular Toxicity of Anticancer Drugs - Papazoglou, Panagiota; Peng, Luying; Sachinidis, Agapios (Frontiers in Cardiovascular Medicine, 2021)
The cardiovascular toxicity of anticancer drugs promotes the development of cardiovascular diseases. Therefore, cardiovascular toxicity is an important safety issue that must be considered when developing medications and therapeutic applications to treat cancer. Among anticancer drugs, members of the anthracycline family, such as doxorubicin, daunorubicin and mitoxantrone, are known to cause cardiotoxicity and even heart failure. Using human-induced pluripotent stem cell-derived cardiomyocytes in combination with “Omic” technologies, we identified several cardiotoxicity mechanisms and signal transduction pathways. Moreover, these drugs acted as cardiovascular toxicants through a syndrome of mechanisms, including epigenetic ones. Herein, we discuss the main cardiovascular toxicity mechanisms, with an emphasis on those associated with reactive oxygen species and mitochondria that contribute to cardiotoxic epigenetic modifications. We also discuss how to mitigate the cardiotoxic effects of anticancer drugs using available pharmaceutical “weapons.”